2006
DOI: 10.1161/circulationaha.105.001313
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial Protection, AT 1 Blockade and Cholesterol-Dependent Oxidative Stress

Abstract: Background-Statins and angiotensin type 1 (AT 1 ) receptor blockers reduce cardiovascular mortality and morbidity. In the Endothelial Protection, AT 1 blockade and Cholesterol-Dependent Oxidative Stress (EPAS) trial, impact of independent or combined statin and AT 1 receptor blocker therapy on endothelial expression of anti-atherosclerotic and proatherosclerotic genes and endothelial function in arteries of patients with coronary artery disease were tested.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
45
1
1

Year Published

2007
2007
2014
2014

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(48 citation statements)
references
References 38 publications
1
45
1
1
Order By: Relevance
“…In the Endothelial Protection, AT1 blockade and Cholesterol-Dependent Oxidative Stress (EPAS) trial, 49 patients undergoing scheduled CABG were randomized to placebo, pravastatin (40 mg/day), irbesartan (150 mg/day), or both for 4 weeks (69). Statin treatment, as well as combination therapy, significantly increases eNOS and suppresses gp91 phox expression in the left IMA, suggesting a synergistic effect on endothelial function, independently of LDL-lowering effects (69). We have recently demonstrated that short-term treatment with atorvastatin rapidly suppresses O 2 -generation and NADPH oxidase activity in SVGs from patients undergoing CABG, independently of LDL-lowering effects (Fig.…”
Section: Fig 4 Effects Of Statins On Enos In Ecsmentioning
confidence: 84%
“…In the Endothelial Protection, AT1 blockade and Cholesterol-Dependent Oxidative Stress (EPAS) trial, 49 patients undergoing scheduled CABG were randomized to placebo, pravastatin (40 mg/day), irbesartan (150 mg/day), or both for 4 weeks (69). Statin treatment, as well as combination therapy, significantly increases eNOS and suppresses gp91 phox expression in the left IMA, suggesting a synergistic effect on endothelial function, independently of LDL-lowering effects (69). We have recently demonstrated that short-term treatment with atorvastatin rapidly suppresses O 2 -generation and NADPH oxidase activity in SVGs from patients undergoing CABG, independently of LDL-lowering effects (Fig.…”
Section: Fig 4 Effects Of Statins On Enos In Ecsmentioning
confidence: 84%
“…Hussein et al demonstrated an additive antioxidant effect when valsartan was co-administered for 2 months to seven hypercholesterolaemic, hypertensive patients taking fluvastatin [40]. The Endothelial Protection, AT1 Blockade and Cholesterol-Dependent Oxidative Stress (EPAS) Trial demonstrated that treatment with pravastatin (40 mg/day), in 60 patients with stable coronary artery disease prior to elective coronary artery bypass grafting, was associated with an increase in the anti-atherosclerotic endothelial expression quotient Q, including mRNA expression (endothelial nitric oxide synthase and CNP divided by lectin-like oxidised LDL receptor-1, and gp91phox in left internal mammary arteries) [41]. Treatment with irbesartan (150 mg/day) had no significant effect.…”
Section: Discussionmentioning
confidence: 99%
“…Treatment with irbesartan (150 mg/day) had no significant effect. However, when combined with pravastatin, it further increased lnQ, but a putative interaction of both therapies on lnQ was not significant [41]. Finally, the Simvastatin/Enalapril Coronary Atherosclerosis Trial (SCAT) examined the effect of simvastatin treatment in 460 normocholesterolaemic patients [42].…”
Section: Discussionmentioning
confidence: 99%
“…Measuring sLOX-1 may be a less invasive tool for the same purpose. In addition, sLOX-1 could be used to evaluate the therapeutic effects, such as administration of statins 38 or angiotensin II receptor blockers, 39 and body weight reduction, 40 because LOX-1 expression has been shown to be reduced by these interventions. However, in the present study plasma levels of sLOX-1 were comparable between patients with prehospital use of ACEI/ARB or statins and those without.…”
Section: 15-18mentioning
confidence: 99%